Stink and the incredible super-galactic jawbreaker - McDonald, Megan; Reynolds, Peter, 1961- (Cambridge, Mass. : Candlewick Press, 2006)
Seven-year-old Stink Moody discovers that he can get free samples by writing letters to candy companies and plans a surprise for his best friend's birthday.
Includes a list of idioms used in the story.
580
Accelerated Reader AR
Keywords: Candy -- Juvenile fiction; Letters -- Juvenile fiction; Schools -- Juvenile fiction; English language -- Idioms -- Juvenile fiction; Humorous stories; Humorous fiction